PENGARUH PENGUATAN GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII MTsS MOHAMAD HEKAL DESA RANTAU ALAI TAHUN AJARAN 2018/2019 - lailatul jannah; ade taufan (Jurnal Tunas Pendidikan, 2019)
The Problems in this research by of shortting result of study IPS from the student of class VIII in MTsS Mohamad Hekal school in Rantau Alai vilage. Motivations study of student to the lesson IPS student of class VIII still minus. One of way which can applied by reinforcement teacher the right student. This research purposes is to anderstand the influence is so significantion of reinforcement teacher of motivation the study IPS from the student of class VIII in MTsS Mohamad Hekal school in Rantau Alai vilage. This reseach is using resoucillation of cuantitative method, whith of date analysis technic thest regresion linier the simple be help the program IBM SPSS 20. The collection date by using inquary to 45 person. Result reseacrh the point getting be able be significantion the reinforcement teachers toward the motivation of study , this result whit by coefisien regresion the beggest 0,975, and determination coefisien (R2) beggest 0,857. Based on the results of the study suggested to the teacher should geve of reinforcement to student in process study, so that it can increase learning motivation study of student optimally.